Dynamics of the 2021 unrest at Changbaishan Tianchi volcano from ALOS-2/PALSAR-2 and seismic data - Lianhuan Wei; Ying Sun; Xingyu Pan; Guoming Liu; Elisa Trasatti; Cristiano Tolomei; Guido Ventura; Christian Bignami; Meng Ao; Shanjun Liu (International Journal of Applied Earth Observations and Geoinformation, 2024)
The Changbaishan Tianchi intraplate volcano is one of the most active and hazardous volcanoes of NE Asia, characterized by a summit caldera formed after the 946 CE ‘Millennium’ Plinian eruption. From December 2020 to June 2021, the frequency and magnitude of earthquakes at Tianchi were significantly higher than during background periods, with hundreds of earthquakes (46 events per month in average) and reaching a local magnitude of ML 3.1. This study reports a comprehensive deformation analysis and geophysical inversion scheme aimed to unveil the dynamics of this period. Multi-temporal InSAR analysis results of 32 ALOS-2 images from 2018 to 2022 show that the surface deformation is a combination of seasonal fluctuations (± 25 mm in average, with a maximum ± 45 mm) and a long-term positive component. The least squares linear regression of the deformation time series and temperature data, isolates the seasonal fluctuations, revealing a clear uplift-subsidence process from June 2020 to July 2021 in the caldera area. To constrain the Tianchi plumbing system dynamics, a combined inversion scheme consisting of three deformation sources is designed. The inversion results and the seismic records indicate that Tianchi volcano has experienced a low-level unrest episode from December 2020 to June 2021. The shallower plumbing system, located at about 5–9 km depth and modelled by pressurized spheroids, underwent a cumulative volume increase of 26 × 106 m3 from November 2018 to April 2021, followed by a volume decrease of 9 × 106 m3 from April to July 2021. This suggests magma uprising from the 14 km deep storage zone to the shallower plumbing system, followed by depressurization of the plumbing system due to the escape of fluids. This research provides a comprehensive understanding of the magma and fluid migration dynamics within the Tianchi multi-level plumbing system for the first time.